Statistics and the Canada Millennium Scholarship Foundation - Kirby, Dale (Canadian Journal of Higher Education, 2002)
This article critiques the Canada Millennium Scholarship Foundation's claim that recent research indicates that "Canada must move beyond (its focus on) student financial assistance" as a means of ensuring access to postsecondary education since "three out of four Canadian youth cite non-financial reasons to explain why they chose not to pursue postsecondary studies." This article argues that the Scholarship Foundation's research claims are not entirely accurate and are presented in a manner that is misleading.